PENGARUH PERSEPSI PASIEN UMUM KELAS 1 TENTANG KUALITAS PELAYANAN TERHADAP CITRA RS HARAPAN BUNDA DI INSTALASI RAWAT INAP - Husaidah, Siti; Radulima, Larince; Haryati, Sri Dewi (Universitas Batam, 2021)
The image is formed from the company carrying out operational activities that have the main foundation in terms of service. This study aims to determine how the patient's perception of the quality of service on the image of Harapan Bunda Hospital. This type of research is quantitative with a cross sectional study approach. The population is all class I patients who are in the inpatient room at Harapan Bunda Hospital, Batam. The sample size is 72 respondents with the calculation of the number of samples using an error rate of 5%. Data were analyzed using chi square test and binary logistics. The results showed that the general patient's perception of the quality of service on the image of the hospital. Harapan Bunda Batam in terms of the dimensions of physical appearance, reliability, responsiveness, friendliness and security, does not have a significant relationship with the value of p= 1,000>Î± (0.05) and the dimensions of competence, trust, access, communication and understanding of customers, have a strong relationship. significant with p value = 0.000 < (0.05). It was concluded that there was no relationship between physical appearance, reliability, responsiveness, friendliness and safety on the image of the hospital. Harapan Bunda Batam and there is a competent relationship, trust, access, communication and understanding of customers to the image of Harapan Bunda Hospital in Batam. It is hoped that improving the quality of service from the dimensions for improving the image of the hospital must be a priority for improving the dimensions that have a strong influence on improving the image of the hospital. but does not neglect image enhancement in other dimensions.